(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Investigation into the possible relationship between the physical features of polypropylene packaging (resistance, welding, perforation, friction coefficient, longitudinal breaking elongation) and resistance to the attacks of III instar larvae of Plodia interpunctella were carried out. The test was carried out on 23 different types of biaxially oriented polypropylene of various thicknesses, currently used for packaging confectionery. Female larvae of Plodia interpunctella can perforate a greater number of packages and carry out more frequent attempts to penetrate the packages than males. After 12 days, both sexes could perforate unprinted films of co-extruded, biaxially oriented polypropylene (17, 20, 25 μm), clear expanded (35, 40 μm) and printed films of co-extruded, biaxially oriented polypropylene (17, 20 μm) acrylic two side coated (20 μm) and clear expanded (40 μm). The printed films of biaxially oriented acrylic two side coated (25, 30 μm) and acrylic two side coated clear expanded (40 μmm), the latter also in the case of unprinted film, were perforated only by females. A relation between the values of the physical tests and the biological ones emerges in the case of longitudinal breaking elongation. The films with values below 50 N/15 mm are perforated, except in the case of unprinted film of acrylic polypropylene two side coated (20, 25 μm). The acrylic coating prevents the aroma of the packaged substance from escaping from the packaging and consequently the larvae are not stimulated to perforate it. On the other hand, film of the same thickness but printed is perforated; the treatment used to print the film decreases the thickness of the acrylic coating and so the aroma can escape through the packaging to the outside.